Dynamic quota calculation system (DQCS): Pricing and quota allocation of telecom customers via data mining approaches - Çelenk, Ulaş; Ertugrul, Duygu Çelik; Zontul, Metin; Elci, Atilla; Uçan, Osman Nuri (IGI Global, 2018)
One of the most important IT sectors that requires big data management is mobile data communication systems (MDCS) of GSM companies. In the charging mechanism of current MDCS, a subscriber "surfs" on the internet that creates data traffic and a counter subtracts the amount of data used by the user from the subscriber's quota. In other words, instant constant quota values are assigned to subscribers without concern for their previous amount of internet usage in current MDCS. Moreover, constant quota values cause constant charge calls in control traffic that are repeated for all new quota requests. Thus, performance degradation occurs because of the repetition of quota request calls and allocations. In this chapter, a dynamic quota calculation system (DQCS) is proposed for dynamic quota allocations and charging in MDCS using data mining approaches as two cascaded blocks. The first block is selforganizing map (SOM) clustering based on a sliding window (SW) methodology followed by the second block, which is the markov chain (MC); the overall system is denoted as "SOM/SW and MC." © 2018, IGI Global.
Keywords: Costs; Data communication systems; Electric charge; Information management; Markov processes; Calculation systems; Charging mechanism; Constant charges; Data traffic; Internet usage; Performance degradation; Sliding Window; Telecom customers; Data mining